KEGIATAN PENGABDIAN MAHASISWA: MENJALIN KOLABORASI UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT TERKHUSUS DI BIDANG PENDIDIKAN - Sri Wahyuni; Nurul Sakinah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to examine how collaboration between students, educational institutions, government, and the community can increase the effectiveness and impact of community service activities at SMPN 12 Barru School, Dusun Watu, Libureng Village, Tanete Riaja District, Barru Regency. The research method used is Documentation Analysis, by collecting and analyzing documents related to student service programs, such as activity reports, evaluations, and documentation of previous activities. This aims to assess the extent to which the goals of the service have been achieved and their impact on the community. The results of the study indicate that the use of student community service activities has a significant impact on the social and economic welfare of the community, as well as providing valuable learning benefits for the students themselves. However, obstacles in the form of limited funds for operational activities, such as transportation, materials, and honorariums for teachers or facilitators, are often insufficient. In addition, the available funds are not always available on time, which can hinder program implementation. Thus, this article also highlights the challenges and opportunities in implementing effective community service, as well as how cross-sector collaboration can increase positive impacts on community welfare in a sustainable manner.